Stimuli responsive polymeric nanocarriers for drug delivery applications : Types and triggers. - Makhlouf, Abdel Salam Hamdy; Abu-Thabit, Nedal Y. (Woodhead Publishing series in biomaterials., 2018)
Stimuli Responsive Polymeric Nanocarriers for Drug Delivery Applications, Volume One: Types and Triggers discusses, in detail, the recent trends in designing biodegradable and biocompatible single-responsive polymers and nanoparticles for safe drug delivery. Focusing on the most advanced materials and technologies, evaluation methods, and advanced synthesis techniques stimuli-responsive polymers, the book is an essential reference for scientists with an interest in drug delivery vehicles. Sections focus on innovation, development and the increased global demand for biodegradable and biocompatible responsive polymers and nanoparticles for safe drug delivery.